The Effect of the Non-compressed Oxygen Therapy and Hyperbaric Oxygenation in Combination With Standardized Drug Therapy on the Blood Acid-Base State Biomarkers in Alcohol Withdrawal Syndrome, an Experimental Study - Kapytau, Dzmitry; Kapytau, Andrei; Khrushch, Inessa; Kudin, Ludmila; Waszkiewicz, Napoleon (Frontiers in Psychiatry, 2022)
In alcohol withdrawal syndrome (AWS), pathophysiological mechanisms cover acid-base disturbances that affect the clinical picture of this state. An earlier study found that oxygen therapy methods in combination with pharmacotherapy improved the cognitive state in persons suffering from AWS. As impairments in the acid-base state influence the general health, timely and effective correction of these acid-base disturbances could result in a potential improvement in the treatment of the alcohol withdrawal symptoms. Therefore, the purpose of this study was to evaluate the effectiveness of non-compressed oxygen therapy (NOT) and hyperbaric oxygenation (HBO) in combination with standard drug therapy (SDT), based on the dynamics of the acid-base state (ABS) in blood during AWS. HBO is the use of oxygen under pressure, whereas NOT uses oxygen without pressure. A comparative assessment of the acid-base state biomarkers was made in 160 patients with a moderate alcohol withdrawal state (3 groups): in patients who underwent SDT only (control group/CG; n=42) and two comparison groups who underwent SDT in combination with NOT (SG1 group; n=56) and HBO (SG2 group; n=62). The use of both oxygen therapy methods (NOT and HBO) in combination with SDT corrected the ABS in a shorter time and more effectively, which was due to the better restoration of the carbonate buffer system. Although we did not find proof that novel oxygen-related therapeutic procedures such as NOT and HBO in combination with standard drug therapy improved the alcohol withdrawal symptoms, it helped with the faster restoration of the acid-base state.